2014
DOI: 10.1007/s10508-014-0263-9
|View full text |Cite
|
Sign up to set email alerts
|

The Invisible Stereotypes of Bisexual Men

Abstract: Bisexual men have little public visibility, yet previous reports indicate that heterosexuals have specific prejudicial attitudes towards them. This article reports on two studies that examined the stereotypical beliefs of heterosexual men and women regarding bisexual men. In Study 1 (n = 88), we examined awareness of social stereotypes (stereotype knowledge). Most of the participants were unable to describe the various stereotypes of bisexual men. Contrary to previous studies, low-prejudiced participants had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 28 publications
(4 reference statements)
8
86
2
11
Order By: Relevance
“…Previous research has suggested that many individuals hold negative attitudes toward bisexuality (Israel & Mohr, 2004), particularly toward bisexual men (Eliason, 2001;Yost & Thomas, 2012). A recent study of heterosexual women's and men's beliefs found that participants used more negative stereotypes to evaluate bisexual men, compared to evaluations of heterosexual and gay men (Zivony & Lobell, 2014). In addition, bisexual individuals have reported experiencing biphobia-negative attitudes about bisexuality-from both heterosexual and sexual minority communities (Mulick & Wright, 2002).…”
Section: Sexual Fluidity and Gendermentioning
confidence: 99%
“…Previous research has suggested that many individuals hold negative attitudes toward bisexuality (Israel & Mohr, 2004), particularly toward bisexual men (Eliason, 2001;Yost & Thomas, 2012). A recent study of heterosexual women's and men's beliefs found that participants used more negative stereotypes to evaluate bisexual men, compared to evaluations of heterosexual and gay men (Zivony & Lobell, 2014). In addition, bisexual individuals have reported experiencing biphobia-negative attitudes about bisexuality-from both heterosexual and sexual minority communities (Mulick & Wright, 2002).…”
Section: Sexual Fluidity and Gendermentioning
confidence: 99%
“…Stereotypes of bisexual people include the belief that they are more sexually experimental and promiscuous than heterosexual or homosexual people, more interested in short-term mating strategies, and more open to new experiences (Israel & Mohr, 2004;Zivony, 2013). Some bisexual men do, in fact, have stronger sexual attractions to and fantasies about both men and women, and are more sexually adventurous than most men (Weinrich & Klein, 2002).…”
Section: Male Bisexual Identity and Sexual Curiositymentioning
confidence: 99%
“…Research suggests negative stereotypes exist about bisexuality, such as: bisexuality does not exist as a sexual identity or as a sexual orientation; and bisexuals are sexually promiscuous (Herek, 2002;Rust, 2002;Zivony and Lobel, 2014). While identity confusion and risky sexual behavior might be associated with maladjustment, there is another possibility: that the negative social reality created by these stereotypes helps explain the greater prevalence of psychological distress among bisexuals.…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that, currently, bisexual individuals face more stigma than homosexual individuals (Zivony and Lobel, 2014), which may be related to monosexism (preference for single-gender orientations) (Ross et al, 2010). For instance, it has been found that heterosexual women hold more negative attitudes towards bisexual than towards lesbian women (Herek, 2002).…”
Section: Introductionmentioning
confidence: 99%